Understanding Parent Support for Physical Activity among Parents of Children and Youth with Disabilities: A Behaviour Change Theory Perspective - Rebecca Bassett-Gunter; Sunita Tanna; Kelly Arbour-Nicitopoulos; Ryan E. Rhodes; Jennifer Leo (European Federation of Adapted Physical Activity, 2020)
Parent support facilitates physical activity among children and youth with disabilities (CYD). Parent physical activity support is a behaviour unto itself which requires motivation and effort, yet its predictors are not well understood. Guided by the theory of planned behaviour (TPB) and multi-process action control (M-PAC) framework, the study aimed to identify predictors of physical activity support among parents of CYD (N = 95; 83.2% female). TPB and M-PAC variables were assessed, followed by parent physical activity support behaviour four weeks later. Regression analysis identified TPB (i.e., perceived behavioural control for child physical activity, intention) and M-PAC (i.e., behavioural regulation, habit, and identity) predictors of parent physical activity support. The inclusion of M-PAC variables into the model explained an additional 18% variance in parent physical activity support. There is value in understanding both pre- and post-intentional predictors of parent physical activity support. This study can inform future research and interventions to support parent physical activity support to facilitate physical activity among CYD.